PSIKOLOGI BENCANA: SEBUAH KAJIAN DALAM MEMITIGASI DAMPAK PSIKOLOGIS PASCA BENCANA BAGI MASYARAKAT URBAN - Rahmat, Hayatul Khairul (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
This study aims to explore the application of disaster psychology in mitigating the psychological impact of post-disaster in urban communities. This study uses a literature study approach. The findings of this study are that the role of disaster psychology is very important in the context of urban communities. Psychological reactions to disasters can be very different between urban and rural communities, so different approaches are needed in post-disaster interventions. Disaster prevention and preparation are also crucial in the urban context, considering the characteristics of urban communities that are vulnerable to disasters.